1991
DOI: 10.1172/jci115440
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of murine type 1 plasminogen activator inhibitor gene expression in vivo. Tissue specificity and induction by lipopolysaccharide, tumor necrosis factor-alpha, and transforming growth factor-beta.

Abstract: The regulation of type 1 plasminogen activator inhibitor (PAI-1) gene expression was studied in vivo employing a murine model system. Nuclease protection analysis revealed relatively high concentrations of PAT-i mRNA in the aorta, adipose tissue, heart, and lungs of untreated CB6 (BalbC X C57B16) mice. Treatment of CB6 mice with LPS, TNF-a, or transforming growth factor-,@ (TGF-ft) increased the steady-state levels of PAM-i mRNA within 3 h in all tissues examined. However, the greatest responses to TGF-ft were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
270
0
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(292 citation statements)
references
References 52 publications
16
270
0
6
Order By: Relevance
“…PAI-1 is a serine protease inhibitor known to bind and inactivate both tissue-type and urokinase-type plasminogen activators (tPA and uPA), respectively . PAI-1 is found in low levels in the adult brain (Sawdey and Loskutoff, 1991), but its expression can be upregulated in astrocytes by stimulation with TGF-β1 and plasminogen (Datto et al, 1995;Buisson et al, 1998). Intravenous tPA has been used to treat acute stroke because of its thrombolytic activity and its ability to restore circulation to the brain (Hacke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 is a serine protease inhibitor known to bind and inactivate both tissue-type and urokinase-type plasminogen activators (tPA and uPA), respectively . PAI-1 is found in low levels in the adult brain (Sawdey and Loskutoff, 1991), but its expression can be upregulated in astrocytes by stimulation with TGF-β1 and plasminogen (Datto et al, 1995;Buisson et al, 1998). Intravenous tPA has been used to treat acute stroke because of its thrombolytic activity and its ability to restore circulation to the brain (Hacke et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Initial clues for such a hypothesis came from the observation that the adipose tissue of the mouse contained relatively high levels of PAI-1 mRNA. 15 Moreover, clinical studies demonstrated that weight loss due to surgical treatment, diet, etc, significantly reduced plasma PAI-1 levels in obese humans. 11,12,16,17 These…”
Section: Adipose Tissue As a Source Of Pai-1 In Obesitymentioning
confidence: 99%
“…13 The expression of TNF-␣ by adipose cells, particularly in the context of obesity, may interfere with certain aspects of insulin signaling, such as the tyrosine kinase activity of the insulin receptor, and thus contribute to insulin resistance. Interestingly, TNF-␣ is known to stimulate PAI-1 biosynthesis by a variety of cultured cells and by many murine tissues in vivo, 3,4,15 and administration of TNF-␣ to lean mice significantly increased PAI-1 mRNA in the adipocytes, adventitial cells, and vascular smooth muscle cells in the adipose tissues (Reference 9; Figs 1 and 2, compare panels A and C). This pattern is similar to the pattern of PAI-1 mRNA observed in the adipose tissues of obese mice (Figs 1 and 2, compare panels B and C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1 or CEP promoter activity did not increase in response to TNFα to levels as high as those reported previously. 19,20 These observations may be explained by the possibility that DNA fragments used in this study may lack the TNFα responsive elements located upstream of the fragment, although one TNFα responsive element does reside in this fragment. 21,22 Based upon data shown in Table 1, the CEP promoter appeared to be 14-fold stronger than the PAI-1 promoter, comparable to the CAG promoter, and had similar responses to TGFβ1 and TNFα with the PAI-1 promoter.…”
Section: Activities and Properties Of Enhanced Pai-1 Promotermentioning
confidence: 90%